The pregc strain of N. crassa has abnormal vesicles when grown on both low- and high-Pi media - S R Nozawa; G Thedei Jr; C H Pellizzon; A Rossi (Fungal Genetics Reports, 2000)
The genetic and molecular mechanisms controlling the synthesis of de-repressible phosphatases in Neurospora crassa include four regulatory genes, nuc-2, preg, pgov, and nuc-1, involved in a hierarchical relationship (Metzenberg, 1979. Microbiol. Rev. 43: 361-383).